Growth Process of Bihar Economy (2005-2015) and Functions of Uttar Bihar Gramin Bank: An Overview - Dr. Swati Kumari; Dr. Abhay Kumar (International Journal of Scientific Research in Science and Technology, 2025)
In this paper, we focused on the recent growth process of Bihar's economy, which has been a strong and sustained one, and its growth rate was one of the highest among all the Indian states. During 2005-06 to 2009-10, the GSDP at constant prices grew at an annual rate of 10.2 percent between 2010-11 and 2013-14, the growth rate was even higher at 10.4 percent. The GSDP of Bihar in 2004-05 was Rs. 0.78 lakh crore in current prices, yielding a per capita income of Rs. 8773. The estimated GSDP at current prices in 2013-14 is Rs 3.43 lakh crore, implying a per capita income of Rs. 33,954.
Keywords: Bihar Economy; RRBs; GDP